Association Between Domain-Specific Physical Activity and Novel Inflammatory Biomarkers Among US Adults: Insights From NHANES 2007–2018 - Xin-ying Liu; Kai Yao (Mediators of Inflammation, 2025)
Conclusions: The impact of different PA domains on systemic inflammation varies significantly. Given the well-established link between chronic inflammation and diseases such as cardiovascular disease (CVD), diabetes, and metabolic disorders, specific recommendations for PA categories should be provided, particularly targeting individuals with high systemic inflammatory responses.